Therapeutic efficacy of rhoifolin in type 2 diabetes mellitus: Effects on metabolic parameters, hepatic function, and oxidative stress: a dose-dependent study - Sndos Z. Fattiny; Manal Abdulaziz Binobead; Abu ElGasim A. Yagoub; Ghedeir M. Alshammari; Ali Saleh; Mohammed Abdo Yahya (Frontiers in Pharmacology)
Background/objectivesDiabetes is one of the most prevalent chronic disorders globally and is linked to obesity. Research has shown that rhoifolin (ROF) can effectively treat metabolic illnesses. This study examines the impact of ROF on glucose and lipid metabolism in a rat model of Type 2 Diabetes Mellitus (T2DM) and investigates its underlying mechanisms.MethodsT2DM was induced in adult male Wistar rats by administering a high-fat diet (HFD) along with a low dose of streptozotocin (STZ) (35 mg/kg, i. p.). All experiments were conducted over 8 weeks. Six rat groups (n = 7 per group) were administered either a vehicle or incremental doses of ROF (10, 20, 40 mg/kg) for the last 4 weeks.ResultsROF significantly improved body weight and protected against hepatic damage and steatosis. It notably reduced plasma glucose, insulin, hemoglobin A1c (HbA1c), and the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR). Serum lipid profiles also improved, with decreases in triglycerides (TGs), cholesterol (CHOL), low-density lipoprotein cholesterol (LDL-c), and free fatty acids (FFAs), and an increase in high-density lipoprotein cholesterol (HDL-c). Hepatic dysfunction was alleviated, as evidenced by normalized levels of aspartate transaminase (AST), alanine transaminase (ALT), and gamma-glutamyl transferase (GGT). ROF reduced inflammation, demonstrated by lower tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) levels and decreased transcription and nuclear accumulation of nuclear factor kappa beta (NF-κB). It also mitigated oxidative stress, evidenced by reduced malondialdehyde (MDA) and increased glutathione (GSH), superoxide dismutase (SOD), and heme oxygenase-1 (HO-1) levels. ROF normalized hepatic peroxisome proliferator-activated receptor alpha (PPARα) and reduced sterol regulatory element-binding protein 1 (SREBP1) activity. Additionally, it modulated apoptosis by decreasing Bax and caspase-3 while increasing Bcl-2. The treatment of ROF improved hepatic glucokinase (GK) activity and lowered glucose-6-phosphatase (G6Pase) levels. These effects were dose-dependent.ConclusionROF shows significant therapeutic potential by enhancing metabolic parameters and modulating key pathways in T2DM, which can pave the way for future animal and clinical intervention studies to validate its therapeutic efficacy and safety.